Upper limb entrapment neuropathies in multiple sclerosis. Issue 2 (June 2020) - Yin, Han; Nair, Krishnan PS; Rao, Dasappaiah G; Hariharan, Sankaranarayanan; Spencer, Amy; Baster, Kathleen
Introduction: Entrapment neuropathies of upper limbs such as carpal tunnel and cubital tunnel syndromes are common in the general population. Identification of entrapment neuropathies of upper limbs in patients with multiple sclerosis can be clinically challenging as signs and symptoms could be attributed to multiple sclerosis. People at later stages of multiple sclerosis use mobility aids and wheelchairs. Weakness of hands in this cohort due to entrapment neuropathies could adversely affect their mobility and independence. Methods: This was a retrospective review of records of patients with multiple sclerosis referred for clinical neurophysiological studies with clinical suspicion of upper limb entrapment neuropathies over a 10-year period. We collected demographic details, clinical features, clinical neurophysiological data and details of aids and appliances used for mobility. Results: Among 71 patients, 38 (53.5%) patients had at least one entrapment neuropathy of upper limb confirmed by clinical neurophysiological studies. Twelve (31%) patients had median nerve entrapment, 20 (53%) had ulnar nerve entrapment and six (16%) had both. Risk of ulnar nerve entrapment was significantly higher in patients using a powered wheelchair (odds ratio 5.7, 95% confidence interval (1.7–18.7, p  = 0.0037). Discussion: Entrapment neuropathies should be considered in patients with multiple sclerosis reporting sensory and motor symptoms of hands.